2005
DOI: 10.1136/jcp.2004.023648
|View full text |Cite
|
Sign up to set email alerts
|

H19 expression in hepatic metastases from a range of human carcinomas

Abstract: Aims: To investigate the expression of the imprinted oncofetal H19 gene in hepatic metastases derived from a range of human carcinomas and assess its prognostic value with the view of developing a DNA based treatment for such metastases. Methods: Non-radioactive in situ hybridisation for H19 RNA was performed on paraffin wax embedded sections of liver biopsies or partial hepatectomy specimens, taken from 80 patients with hepatic metastases derived from carcinomas from several medical centres in Israel. The deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 33 publications
(37 reference statements)
1
46
0
1
Order By: Relevance
“…50 Adriaenssens et al 51 have suggested that H19 has a role in epithelialmesenchymal interactions and thus in morphogenesis and/or migration of epithelial cells. A previous study has shown that H19 is highly expressed in hepatic metastases from a range of human carcinomas, 52 although the underlying mechanism has not been clearly shown. A recent study suggested that upregulated H19 enhances bladder cancer metastasis by associating with EZH2, resulting in Wnt/b-catenin activation and the subsequent downregulation of CDH1.…”
Section: Malat1 H19 and Ccat2-wnt/b-catenin Pathwaymentioning
confidence: 99%
“…50 Adriaenssens et al 51 have suggested that H19 has a role in epithelialmesenchymal interactions and thus in morphogenesis and/or migration of epithelial cells. A previous study has shown that H19 is highly expressed in hepatic metastases from a range of human carcinomas, 52 although the underlying mechanism has not been clearly shown. A recent study suggested that upregulated H19 enhances bladder cancer metastasis by associating with EZH2, resulting in Wnt/b-catenin activation and the subsequent downregulation of CDH1.…”
Section: Malat1 H19 and Ccat2-wnt/b-catenin Pathwaymentioning
confidence: 99%
“…H19 was found highly expressed and /or manifest aberrant allelic pattern of expression in over 30 types of cancer (14). Investigation of the expression of the H19 gene in hepatic metastases derived from a range of human carcinomas showed that H19 is highly expressed in the majority of hepatic metastases tested (18). Moreover, in the first report on the importance of the Twist gene product in tumor metastasis, the investigators showed that H19 is the highest differentially expressed gene in metastatic tumor cell lines investigated (19).…”
Section: Discussionmentioning
confidence: 97%
“…H19 is an imprinted oncofetal gene, and loss of imprinting at the H19 locus resulted in over-expression of H19 in cancers of the esophagus, colon, liver, bladder and hepatic metastases (Hibi et al, 1996;Fellig et al, 2005;Matouk et al, 2007). H19 has been implicated as having both oncogenic and tumor suppression properties in cancer.…”
Section: Discussionmentioning
confidence: 99%